2017
DOI: 10.1089/mdr.2015.0272
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds as Inhibitors of Tyrosyl-tRNA Synthetase

Abstract: Tyrosyl-tRNA synthetases (TyrRSs) as essential enzymes for all living organisms are good candidates for therapeutic target in the prevention and therapy of microbial infection. We examined the effect of various polyphenols, alkaloids, and terpenes-secondary metabolites produced by higher plants showing many beneficial properties for the human organism, on bacterial aminoacylation reaction. The most potent inhibitors of Escherichia coli TyrRS are epigallocatechin gallate, acacetin, kaempferide, and chrysin, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Besides their antiparasitic effects, ARS inhibitors also played an important role in the antibacterial and antifungal processes [45][46][47][48] . By evaluating the inhibitory effect of a series of 3-aminomethyl 4-halogen benzoxaboroles on Mtb leucyl-tRNA synthetase (LeuRS), Li et al 49 found that one of the compounds, GSK656, was highly selective for Mtb LeuRS and had good antitubercular activity and tolerability in the mid-nanomolar range.…”
Section: Pathogen Arss Serve As Anti-infective Targetsmentioning
confidence: 99%
“…Besides their antiparasitic effects, ARS inhibitors also played an important role in the antibacterial and antifungal processes [45][46][47][48] . By evaluating the inhibitory effect of a series of 3-aminomethyl 4-halogen benzoxaboroles on Mtb leucyl-tRNA synthetase (LeuRS), Li et al 49 found that one of the compounds, GSK656, was highly selective for Mtb LeuRS and had good antitubercular activity and tolerability in the mid-nanomolar range.…”
Section: Pathogen Arss Serve As Anti-infective Targetsmentioning
confidence: 99%
“…Acacetin, a natural flavone widely distributed in plant pigments, has been shown by many studies to have multiple beneficial biological effects in cancers, 9,10 cardiac remodelling, 11 microbial infections, 12 inflammation 13 and oxidative stress 14 . In human umbilical vein endothelial (HUVEC) cells, acacetin inhibited E‐selectin expression through the p38/MAPK pathway and activation of the nuclear factor NF‐κB 15 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge there are no reports for antimicrobial activity of jaceidin and centaureidin against methicillin-resistant S. aureus . Skupińska et al ( 2017 ) reported that the most active inhibitors of E. coli and S. aureus had a –OH groups at 5- and 7- positions and methoxy group at C-4′, such as kaempferide with MIC 50 values of 22.7 µg/mL and 8.5 µg/mL, respectively. Also, authors reported that kaempferol was inactive against E. coli , while in the study of Wu et al ( 2013 ) it was reactive with MIC 50 value of 25 µg/mL, whereas authors indicated that hydroxyl group at C-4′ are necessary for the activity.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic, caffeic, p -coumaric and chlorogenic acid exhibited significant inhibitor activity against S. aureus and MRSA (Rivero-Cruz, 2008 ; Özçelik et al 2011 ; Dimkić et al, 2016 ). It was shown that flavonoids exhibit better activity than phenolic acids against E. coli (Rivero-Cruz, 2008 ; Liu et al 2013 ; Wu et al 2013 ; Skupińska et al 2017 ). In our study, this link is also visible through the presence of flavonoids and phenolic acids in the extracts, whereas methoxylated flavonoids found with highest intensities in EtOAc extract, which expressed the best activity towards E. coli .…”
Section: Discussionmentioning
confidence: 99%